The relationship between intestinal microbiota and polycystic ovary syndrome - Korabiusz, Katarzyna; Wawryków, Agata; Fabian- Danielewska, Anna; Stecko, Monika; Piątek, Patrycja; Żukowska, Magdalena (Journal of Education, Health and Sport, 2019)
Introduction: PCOS is a hyperandrogenic and low-pathogenic disease and patients suffering from PCOS have significantly lower intestinal microbiota variation in comparison with healthy individuals.Aim of the study:The aim of the work is to overview the literary production regarding reliance between intestinal microbiota and polycystic ovary syndrome.Conclusions: Results of the research show change in microbiome data amongst women suffering from polycystic ovary syndrome.